check the picture below
so... the center coordinates of the circle, are the Midpoint of both ends, thus we can simply use the MidPoint equation to get it
[tex]\bf \textit{middle point of 2 points }\\ \quad \\
\begin{array}{lllll}
&x_1&y_1&x_2&y_2\\
% (a,b)
&({{ 2}}\quad ,&{{ -1}})\quad
% (c,d)
&({{ x}}\quad ,&{{ y}})
\end{array}\qquad
% coordinates of midpoint
\left(\cfrac{{{ x_2}} + {{ x_1}}}{2}\quad ,\quad \cfrac{{{ y_2}} + {{ y_1}}}{2} \right)
\\\\\\
\left(\cfrac{2+x}{2}\quad ,\quad \cfrac{-1+y}{2} \right)=(0,-2)\implies
\begin{cases}
\frac{2+x}{2}=0\\
2+x=0\\
\boxed{x=-2}\\
-------\\
\frac{-1+y}{2}=-2\\
-1+y=-4\\
\boxed{y=-3}
\end{cases}[/tex]